Reassessing a Distinctive Macedonian Article Feature: Multiple Determination (MP) is not that Multiple? - Karapejovski, Boban (My University, 2023)
Traditionally, in Macedonian grammar, primarily in the morphology but also in the syntax, the Macedonian article is defined as morphologically bound (suffixes; also, clitics, by some authors, e.g. Мишеска-Томиќ 2008; Hopper and Traugott 1993) and tripartite: it appears in its neutral, proximal, and distal variety. In a few articles this characteristic is disputed and revised (Тополињска 2006; Линдстет 2013; Карапејовски 2017; Карапејовски 2023). Examples such as: Го видо-в тоа дете-то. Itobj.neuter see-I1SG.past that kid-thedef.art.neutral ‘I saw that kid.’ in the literature are called “double determined” or “multiple determined”. In Macedonian, explanations of some of the aspects of our topic can be found back in Ugrinova-Skalovska’s article from 1961 (Угринова-Скаловска 1961), but also in Minova-Gjurkova (Минова-Ѓуркова 1991; Минова-Ѓуркова 2000), and Topolinjska. However, this topic is reexamined in the past decade by Alexiadou (2014) for Greek, Rudin (2018a; 2018b), Friedman (Фридман 2016), and Joseph (2019) for various aspects and in the Balkan context. 47 Since newly published articles have reignited the interest in this issue, we reconsider the topic in this paper. Our goal is to provide an analysis of corpora in order to answer the questions of the origin, as well as the syntactical and semantical ‘behaviour’ of this construction. We shall propose two hypotheses. The first one, regarding the origin, is that, although widely accepted that the Balkan sprachbund played a significant role, the language system should have some internal possibilities for its development. The second, about the syntax and the semantics – there are three options, if we build on the formal view that there are multiple determined NPs to the propositional content of the utterance: a) grammaticalization of an element of the noun phrase, so the other element takes its semantics and function; b) lexicalization – next level of grammaticalization: the element is so much desemantized that it becomes part of a lexeme; c) one of the elements is turned into modal/affective particle (cf. Dučevska and Karapejovski 2022). References Alexiadou, Artemis. 2014. Multiple Determiners and the Structure of DPs. Amsterdam – Philadelphia: John Benjamins Publishing. Dučevska, Aneta and Boban Karapejovski. 2022. “Demonstratives in Bombs: From Units of Reference to Particles.” 11th Macedonian-North American Conference on Macedonian Studies (MNACMS). Arizona: The Melikian Center, Arizona State University. [presentation] Hopper, Paul J. and Elizabeth Closs Traugott. 1993. Grammaticalization. Cambridge: Cambridge University Press. Joseph, Brian D. 2019. “Multiple Determination in Greek and the Balkans”. Balkanistica, 32.1: 171–183. Rudin, Catherine. 2018a. “Multiple Determination in Bulgarian and Macedonian: An Exploration of Structure, Usage, and Meaning”, In: Stephen M. Dickey and Mark Richard Lauersdorf, eds. V zeleni drželi zeleni breg: Studies in Honor of Marc L. Greenberg, 263–286. Bloomington: Slavica Publishers. Rudin, Catherine. 2018b. “On DP Structure in Balkan Slavic: Evidence from Multiple Determination”, In: FASL 27, 418–437. Michigan: Michigan Slavic Publications. Карапејовски, Бобан. 2017. „Показните заменки наспрема морфолошки врзаниот член како експоненти на категоријата определеност во македонскиот јазик“. Прилози на Одделението за лингвистика и литературна наука на МАНУ XLII 1–2, 5–18. Скопје: Македонска академија на науките и уметностите. Карапејовски, Бобан. 2022. „Развојот на постпозитивниот морфолошки член во македонскиот јазик како експонент на генеричната референција“, Slovene Vol. 11, № 2, 244–263. Москва: Москва: Институт славяноведения РАН; Институт русского языка им. В. В. Виноградова РАН. 48 Карапејовски, Бобан. 2023. Јазикот и определеноста : експонентите на категоријата определеност во македонскиот јазик. Скопје: Ми-Ан. Линдстет, Йоуко. 2013. Маркери на определеността на именната група в историята на българския език. (Достапно на: https://tuhat.halvi.helsinki.fi/portal/en/activities/third-international(c3e62ada-defa-4774-9750-335292585ada).html, пристапено на: 2.1.2020) Минова-Ѓуркова, Лилјана. 1991. „За разговорниот јазик на македонските родени говорители“. Литературен збор, 1–2. Скопје: Сојуз на друштвата за македонски јазик. Минова-Ѓуркова, Лилјана. 2000. Синтакса на македонскиот стандарден јазик. Скопје: Магор. Мишеска-Томиќ, Олга. 2008. Македонските клитики во балканското окружение. Скопје: Македонска академија на науките и уметностите. Тополињска, Зузана. 2006. „Тројниот член – да или не“. Јужнословенски филолог, 62, 7–15. doi: 10.2298/JFI0662007. Угринова-Скаловска, Радмила. 1961. „Две стилски особености во нашиот говорен јазик“. Македонски јазик, XI–XII, кн. 1–2, 105–111. Скопје: Институт за македонски јазик „Крсте Мисирков“. Фридман, Виктор. 2016. „Една стилска особеност во македонскиот говорен јазик во XXI век: двојно определување во таканаречените ‘Бомби’ од 2015 г.“, Во: Зборник во чест на Радмила Угринова-Скаловска по повод деведесетгодишнината од раѓањето. Скопје: Универзитет „Св. Кирил и Методиј“ во Скопје, Филолошки факултет „Блаже Конески“.